IMPROVEMENT OF WATER ALLOCATION EFFICIENCY IN THE AMU-SURKHAN RIVERS BASIN - Malika Ikramova; Khairullo Kabilov; Alisher Khodjiev; Ifoda Akhmedkhodjaeva; Dilshod Nazaraliev (World Science, 2019)
In the article efficiency of water distribution in the territory of Amu-Surkon basin is analysed and based on the results, provided the recommendations. The study is conducted within the project QH-A-QH-2018-409 “Increase efficiency of water resources management in Surkhandarya region: improve interbasin re-distribution of the water resources of Surkhandarya and Sherabaddarya Rivers” funded by Uzbekistan government. The main problems of water management in the Surkhandarya region are: outdated irrigation systems requiring an urgent modernization; large dependence on pump irrigation; low energy efficiency of pumping stations due to use of the old high energy-consuming equipment; irrational distribution and large unproductive technical and operational water losses. Increase of sensitivity to climate change with forecasting of 50% water deficit by 2050 leads to drought and further desertification, including impact on food security. In the article some results are introduced related to improve water allocation by redistribution of water resources between the river basins in the region aimed to reduce of pumped water use for irrigation.